Correlation of Weight Gain during Pregnancy and Onset of Lactation - Yuli Trisetiyono; Ursheila Haekmatiar (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Pregnancy is associated with weight gain. An increase beyond the recommendation of the Institute of Medicine (IOM), has consequences for pregnancy, childbirth, even postpartum. One result of postpartum is a delayed onset of lactation. This study aimed to evaluate the relationship between weight gain during pregnancy and the onset of fluency lactation. The design was observational analytic with a cross-sectional approach which was carried out on postpartum mothers conducted in six primary health centers in the area of Semarang City. The researchers recorded data from the antenatal care book and a questionnaire on the first postpartum visit. The data was analyzed bivariately using Chi-square test. From 89 subjects, 41 people (46%) experienced under-recommendation weight gain during pregnancy, 32 people (36%) according to recommendations, and 16 people (18%) above recommendations. The onset of fluent lactation since the first 24 hours was found in 28 people (31.5%), 41 people (46.1%) start from day 1-7, and 20 people (22.5%) never went fluently until one week postpartum were. Chi-square test showed that the results were not significant (p=0.215). There was no significant relationship between weight gain during pregnancy and the onset of fluency lactation.